2020
DOI: 10.1101/2020.09.10.290890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association and prediction study in grapevine deciphers the genetic architecture of multiple traits and identifies genes under many new QTLs

Abstract: SummaryTo cope with the challenges facing agriculture, speeding-up breeding programs is a worthy endeavor, especially for perennials, but requires to understand the genetic architecture of important traits. To go beyond QTL mapping in bi-parental crosses, we exploited a diverse panel of 279 Vitis vinifera L. cultivars. This panel planted in five blocks in the vineyard was phenotyped over several years for 127 traits including yield components, organic acids, aroma precursors, polyphenols, and a water stress in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 142 publications
0
16
0
Order By: Relevance
“…cereal crops), due to the lower costs of high-throughput sequencing and phenotyping techniques. Recently, GWAS analyses of 472 Vitis accessions ( Liang et al, 2019 ) and 279 V. vinifera L. cultivars ( Flutre et al, 2020 ), were employed to identify loci associated with traits including TA accumulation, detailed further in Section 9.…”
Section: Tartaric Acid Accumulation In Grape Berries (Concentration Amentioning
confidence: 99%
See 1 more Smart Citation
“…cereal crops), due to the lower costs of high-throughput sequencing and phenotyping techniques. Recently, GWAS analyses of 472 Vitis accessions ( Liang et al, 2019 ) and 279 V. vinifera L. cultivars ( Flutre et al, 2020 ), were employed to identify loci associated with traits including TA accumulation, detailed further in Section 9.…”
Section: Tartaric Acid Accumulation In Grape Berries (Concentration Amentioning
confidence: 99%
“…Experimental evidence is required before we can further speculate on their potential functions in TA biosynthesis. In addition, another comprehensive GWAS analysis of 279 V. vinifera L. cultivars also identified loci associated with TA accumulation ( Flutre et al, 2020 ), although at this stage there is insufficient publicly available data to link this to a specific gene or set of genes.…”
Section: Identifying New Candidates For the Remaining Steps Of Ta Biomentioning
confidence: 99%
“…The reported PA for mbw was 0.56, whereas in the present study, we obtained 0.35 in the Grenache x Syrah progeny (n=59). We further investigated such discrepancy, and found it related to a sampling bias due to the small VS size in Flutre et al 26 (data not shown).…”
Section: Range Of Pa Valuesmentioning
confidence: 88%
“…Yet, Mendelian sampling PA was still quite high, considering that TS was essentially unrelated to VS, i.e., with no first-degree relationship with predicted progenies. The same diversity panel was previously used in Flutre et al 26 for predicting individual genotypic values of 23 additional Syrah x Grenache offspring. The reported PA for mbw was 0.56, whereas in the present study, we obtained 0.35 in the Grenache x Syrah progeny (n=59).…”
Section: Range Of Pa Valuesmentioning
confidence: 99%
See 1 more Smart Citation